New approach to produce absorbent pads for new end uses - (:unkn) unknown (WOODHEAD PUBL LTD, 2006)
The use of hygiene pads is increasing rapidly. They are used for baby's diapers, sanitary products and incontinence pads for the elderly etc. But the use of pads with a dual mission of healing and protecting by absorbing the discharged liquid whilst releasing healing cream or chemical to the infected area without mixing the discharged liquid with the healing chemical is a relatively new one. In this study a new novel approach has been tested in the care for wounds, haemorrhoids etc.